PROSES REDUPLIKASI DALAM BAHASA INGGRIS - Ida Ayu Made Puspani (Program Magister Linguistik Universitas Udayana, 2010)
Morphological study covers the words formation process such as: derivation, affixation, reduplication and compound. The word formation in every language is the creativity in the forming of new words from the words that are already existed within the language. This writing aims at describing the word formation in English specially reduplication. The data of this writing was taken from English dictionary in order to give description that English has reduplication (words formation) though the numbers are not as many as other types of word formation (affixation, derivation and compound) Reduplication in English shows the change of word identity and the change of category (word class) like in `roly-poly` ( means pudding/noun) which has the base form `poly` means (polytechnic/noun); though the category of `roly poly` and ` poly` are the same (noun) but they have different identity. The change of category happens on the reduplication `hangky-panky`(trickery/adjective) which has the base form `hanky`(handkerchief/noun); it has the change of category from noun becomes adjective.